Keputusan Menjadi Nasabah Bank Syariah: Peran Literasi Keuangan Syariah, Kepercayaan, dan Citra Bank Syariah - Setiawan Setiawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Islamic banks in Indonesia have existed in Indonesia for three decades. However, until now the development is not very significant. Even though Muslims are the majority population in Indonesia. The purpose of this study was to investigate how three factors - Islamic financial literacy, trust in Islamic banks, and the image of Islamic banks - impact the decision to become a customer of Islamic banks. The research employed a quantitative approach and explanatory research to collect primary data from 200 respondents with diverse backgrounds through questionnaires. The study found that a higher level of Islamic financial literacy can motivate individuals to choose Islamic banks as customers. This finding highlights the importance of enhancing public awareness and understanding of Islamic finance. Additionally, the trust and image of Islamic banks were identified as critical factors affecting customers' decisions. Therefore, it is vital for Islamic banks to maintain high levels of professionalism to sustain customer trust and present a positive image.